Constructing a Life–quality Scale for the teachers of Jordanian ministry of education - aldarabeh, Odeh mohammad Abdullah (Journal of Educational and Psychological Sciences, 2021)
his study aimed at building a life quality scale for teachers working in the Jordanian Ministry of Education. This study was conducted in schools affiliated with the Jordanian Ministry of Education, and the researcher used the descriptive approach in this study, and the scale of the study was built then its validity and reliability were confirmed and applied to the study sample, which involved 1780 teachers who were selected by random cluster method from six directorates of education Distributed in three regions, and the results of the study showed that there are statistically significant differences in the level of life quality attributed to the variable of the region and in favor of the central and northern regions. The research came out with several recommendations, most notably the re- application of the scale to other categories, knowing its validity and stability, and the derivation of its criteria.